The effect of sustainable development on environmental agenda. Case study: Putrajaya Green City, Malaysia - Md Hanafiah, Faizal; Azmi, Muhammad Aqmarul Azri; Ibrahim, Siti Halipah; Md Zan, Zainal (2020)
During the past four decades, the relationship between the evolution of development strategies and environmental concerns within the urban context. Sustainable development is popularly described as a development that meets the needs of the present without compromising the ability of the future generations to meet their own needs. This study is a descriptive research that emphasis to the elaboration of an issue of concern and interest in relation to the implementation of the Green City Program in Putrajaya, Malaysia. This research will use a qualitative study and rely on analytical approach which data were collected from research report, government annual audit report, scientific article and reliable resources. There are TWO (2) indices form Malaysian initiatives for the performance of sustainable development policies namely 1) Malaysian Quality of Life Index MQLI and 2) Malaysian Urban Sustainability Indicator Network MURNInet. According to MQLI Report 2011 by Economic Planning Unit EPU, the quality of life in Malaysia has improved during the 2000 to 2010 period. Components measured in MQLI such as education, transport, communication, culture and leisure, public safety, health and social participation recorded improvement. Overall performance of MQLI was in line with the national aspiration to achieve high-income developed nation by the year 2020. According to MURNInet 2013, Putrajaya sustainable status with a share of 82.0% indicates that the development of existing and future Putrajaya in line with its goal to achieve the status of Green City Putrajaya 2025. This research concludes that the level of implementation of the sustainable development of Putrajaya Green City is still in the initial phase. Lack of knowledge of this concept is also at a satisfactory level.